2021
DOI: 10.3389/fmats.2021.798726
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Neural Network for Real-Time Crack Detection on Concrete Surface in Fog

Abstract: Cracks are one of the most common factors that affect the quality of concrete surfaces, so it is necessary to detect concrete surface cracks. However, the current method of manual crack detection is labor-intensive and time-consuming. This study implements a novel lightweight neural network based on the YOLOv4 algorithm to detect cracks on a concrete surface in fog. Using the computer vision algorithm and the GhostNet Module concept for reference, the backbone network architecture of YOLOv4 is improved. The fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…YOLOv3-Lite [26] uses the deep separable convolution to extract features, and utilizes the feature pyramid to preserve semantic information at different levels. A crack detection method based on the YOLOv4 algorithm is proposed in [34], which achieves good crack detection results with a lower trained model weight. To overcome the complicated and uneconomical disadvantages of traditional crack detection methods, a pavement crack detection network [35] is proposed to combine YOLOv5 and Transformer.…”
Section: Related Work 21 Crack Detectionmentioning
confidence: 99%
“…YOLOv3-Lite [26] uses the deep separable convolution to extract features, and utilizes the feature pyramid to preserve semantic information at different levels. A crack detection method based on the YOLOv4 algorithm is proposed in [34], which achieves good crack detection results with a lower trained model weight. To overcome the complicated and uneconomical disadvantages of traditional crack detection methods, a pavement crack detection network [35] is proposed to combine YOLOv5 and Transformer.…”
Section: Related Work 21 Crack Detectionmentioning
confidence: 99%
“…Research has shown that the You Only Look Once (YOLO) series algorithm performs outstandingly among many object detection networks (Du et al, 2021). In the YOLO model, integrating the attention module or improving the feature extraction network can enhance the sensitivity of the model to the target features (Yao et al, 2019;Yang et al, 2022a;Liu et al, 2022;Zhang et al, 2023a;Kao et al, 2023); combining the depth-separable convolution or replacing the lightweight feature extraction network, a lightweight target detection network for real-time detection of cracks on the structure surface can be obtained (Zhang et al, 2020a;Yao et al, 2021a;Yang et al, 2022b;Zhang et al, 2022;Zhang et al, 2023b;Jin et al, 2023); introducing the focal loss function or transfer learning can improve the recognition accuracy of the model. Deep learning has been gradually applied to bridge crack detection (Zhang et al, 2020b;Yao et al, 2021b;Teng et al, 2022).…”
mentioning
confidence: 99%